Time-dependent reliability analysis of the suspender in half-through arch bridge considering temperature effect. (December 2022) - Zhou, Xiaohang; Elchalakani, Mohamed; Li, Qixuan; Ou, Junjie; Deng, Nianchun; Zhou, Yiming
Abstract: In half-through arch bridges, suspenders are vulnerable components and their service lives are usually far below the expectation. In order to avoid collapse accidents, it is critical to estimate their service lives accurately. Due to the special structural form of half-through arch bridges, temperature can cause an additional lateral bending on the suspenders and shorten their service lives. Neglecting the effect of temperature will make the prediction of suspenders' service lives inaccurate. In this paper, the effect of temperature on the suspenders of half-through arch bridges is investigated, and the service live of the suspenders is estimated based on the time-dependent reliability theory. A large span half-through arch bridge is taken as a case study. The service lives of its short suspenders are estimated, and the results with and without considering the temperature effect are compared. The results indicate that the service life of the shortest suspender is shortened around 7% considering the effect of lateral bending caused by temperature, and the temperature effect should not be neglected.